Uterine myomatosis at the "Enrique C. Sotomayor" gynecological-obstetric hospital from 1985 - 1991 - Dáher Nader, Jorge Elías; Jaramillo, Angela (Revista Universidad de Guayaquil, 1991)
1,016 patients were studied from April 1985 to April 1991, grouping them according to age, history of pregnancy, parity, abortions and cesarean sections, symptoms and signs on Admission, clinical diagnosis, complementary diagnostic means: ultrasound and laparoscopy, characteristics of the tumor: location, type and secondary modifications, anatomical-pathological diagnosis, preoperative complications, surgical treatment and mortality.